Differential diagnosis of vergence and saccade disorders in dyslexia - Lindsey M. Ward (Nature Portfolio, 2020)
Abstract Previous studies suggest vergence and saccade abnormalities in dyslexic adolescents. However, these studies are mainly clinically based and do not provide objective measurements of eye movements, but rather subjectively evaluate vergence using haplosopic conditions in which the two eyes are dissociated (via polarizers, prisms, or intermittent spectacles). Other studies have identified deficits with binocular coordination during reading in dyslexics. Yet, there are few studies that provide objective measurements of eye movements in the dyslexic population to help provide more information regarding if these deficits could be due to an intrinsic motor problem or if they are the consequence of poor reading. 47 dyslexic adolescents (18 female, 29 male; mean age 15.5) and 44 non-dyslexic adolescents (22 female, 22 male; mean age 14.8) wore a head-based eye tracker (PupilCore, Pupil Labs, Berlin) which recorded wide angle saccade and vergence eye movements at 200 Hz. Tests were run using the REMOBI device, which produced a saccade or vergence audiovisual target. Analysis of eye movements was performed with lab-developed software, AIDEAL. The results showed statistically significant abnormalities in vergence and saccades. In vergence, dyslexics displayed a reduced amplitude of the visually driven portion of convergence and a longer duration in the initial phase of divergence. In saccades, dyslexic adolescents demonstrated slower saccades in both directions. They also had an increased disconjugate drift in the first 80 or 160 ms following saccades to the right, suggesting poor binocular coordination. For both vergence and saccades, the peak velocity and time to peak velocity was higher and earlier, respectively, in non-dyslexics compared to dyslexics; yet the average velocity of both movements was lower in dyslexics. Thus, these results indicate peculiar velocity profiles in dyslexics, particularly a slow deceleration phase in both vergence and saccades. The study provides an objective method to diagnose vergence and saccade abnormalities while viewing targets in the real three-dimensional space in a dyslexic population. Vergence abnormalities are demonstrated to be a problem in dyslexics, occurring independently from reading. We hypothesize these disconjugate drifts following saccades are the result of slow vergence capacity. Rehabilitation programs, such as those using REMOBI, should aim to target these deficits in vergence velocity, as this has been shown to improve binocular control.